2010
DOI: 10.4067/s0717-95022010000400019
|View full text |Cite
|
Sign up to set email alerts
|

Histopathological Effects of Aloe barbadensis and Soybean Oil on Rat Liver

Abstract: Barbadensis, which is a species of Aloe vera, is a popular plant used by the common people and in alternative medicine. This study aimed to analyze the effects of Aloe Barbadensis and soybean oil on liver. For this study Wistar Albino female rats were taken and divided into 3 equal groups; the first group was the control group wherein no treatment was applied, second group in which the dissolved form of A. barbadensis in the soybean oil was applied (25 mg/day), and the third group which only soybean oil was ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 27 publications
1
4
0
1
Order By: Relevance
“…The measurement of antioxidant capacity is an appropriate indication for the total antioxidant defences of various kinds of tissues and organs (Ferrara, Gerber & LeCouter, 2003). Our study showed a reduced antioxidant capacity in rats treated with the dyes that can be attributed to the accelerated production of free radicals during (Kosif et al, 2010;Ramos et al, 2015). Meanwhile, the marked increase in infiltration of leucocytes implies a possible inflammatory response in affected tissues, as noted in earlier works (Soltan & Shehata, 2012;El-Desoky et al, 2017) following exposure to synthetic colouring agents in foods.…”
Section: Manuscript To Be Reviewedsupporting
confidence: 78%
“…The measurement of antioxidant capacity is an appropriate indication for the total antioxidant defences of various kinds of tissues and organs (Ferrara, Gerber & LeCouter, 2003). Our study showed a reduced antioxidant capacity in rats treated with the dyes that can be attributed to the accelerated production of free radicals during (Kosif et al, 2010;Ramos et al, 2015). Meanwhile, the marked increase in infiltration of leucocytes implies a possible inflammatory response in affected tissues, as noted in earlier works (Soltan & Shehata, 2012;El-Desoky et al, 2017) following exposure to synthetic colouring agents in foods.…”
Section: Manuscript To Be Reviewedsupporting
confidence: 78%
“…Inflammation, necrosis and vacuolisation of the tubular epithelium occurred, in addition to the destruction of glomeruli, with thickening of Bowman’s capsule. The hydropic degeneration of hepatocytes and vacuolisation of tubular cells indicate the occurrence of intracellular oedema, as a result of toxicity or immune aggressions ( Kosif et al, 2010 ; Ramos et al, 2015 ). Meanwhile, the marked increase in infiltration of leucocytes implies a possible inflammatory response in affected tissues, as noted in earlier works ( Soltan & Shehata, 2012 ; El-Desoky et al, 2017 ) following exposure to synthetic colouring agents in foods.…”
Section: Discussionmentioning
confidence: 99%
“…The hydropic degeneration refers to the occurrence of reversible intracellular edema as a consequence of toxic, infectious or immune aggressions. The increase in cell volume and clearness is associated with the formation of microvacuoles or clear cytoplasmic spaces as a result of the action of injurious agents that cause intracellular accumulation of sodium and increase in water content [13] . These lesions were observed in the liver of all d -limonene-treated rats at both dose levels (25 and 75 mg/kg), but not in control and ethanol-treated animals.…”
Section: Discussionmentioning
confidence: 99%